Waterproof protection treatment method and application of cable sheath PVC (polyvinyl chloride) material

By using carbon tetrafluoride plasma discharge technology to modify PVC materials, the problem of degradation of hydrophobicity of PVC materials in harsh environments is solved, and efficient and environmentally friendly hydrophobic modification effect is achieved, which is suitable for industrial applications.

CN119735832APending Publication Date: 2025-04-01ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411775217.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing PVC materials are prone to decrease hydrophobicity in harsh environments, and traditional hydrophobic protection methods have defects such as environmental protection problems, high costs, and poor uniformity, making it difficult to meet high environmental protection requirements and large-scale industrial applications.

Method used

Carbon tetrafluoride is used as the working fluid gas for plasma discharge, and the PVC material is modified with dielectric barrier discharge technology. By regulating the distribution of fluorine elements and surface roughness, efficient hydrophobic modification of PVC material is achieved.

Benefits of technology

It significantly improves the hydrophobicity and weather resistance of PVC materials, achieves rapid adjustment of fluorine distribution, reduces environmental risks, is suitable for application scenarios with high environmental protection requirements, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735832A_ABST
    Figure CN119735832A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of PVC material processing, and discloses a cable sheath PVC material waterproof protection treatment method and application, the method comprises the following steps: using carbon tetrafluoride as a working medium gas for plasma discharge, using a predefined plasma modification platform and combining a dielectric barrier discharge technology to carry out modification treatment on a PVC material, and obtaining a modified PVC material; the modified polyvinyl chloride material is obtained; carrying out physical and chemical property test on the modified polyvinyl chloride material to obtain a surface energy change state, carrying out hydrophilic angle test on the modified polyvinyl chloride material based on the surface energy change state, and regulating the hydrophilicity of the polyvinyl chloride material according to a hydrophilic angle test result; and sequentially carrying out pulse current attenuation test and breakdown voltage band test on the modified polyvinyl chloride material by utilizing a pulse current attenuation technology. Fluorination treatment is performed on the PVC surface through a CF4 plasma technology, so that the hydrophobicity and weather resistance of PVC are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC material processing, and in particular to a waterproof protection processing method for a cable sheath PVC material and an application thereof. Background Art

[0002] PVC (polyvinyl chloride) materials are widely used in industry and daily life, and are often used in pipes, cable sheaths, building materials and other fields. However, since the surface of PVC materials easily absorbs moisture and dust, when used outdoors, rain, moisture, pollutants, etc. easily adhere to the surface, causing accelerated aging of the material, performance degradation and even failure. Therefore, improving the hydrophobicity of PVC has become an important technical means to improve its durability and stability.

[0003] Hydrophobicity refers to the ability of a material surface to repel water, usually measured by the contact angle. A highly hydrophobic PVC surface can effectively reduce the adhesion of water, thereby preventing hydrolysis, mold growth, and pollutant deposition. For outdoor applications, improving the hydrophobicity of PVC can significantly enhance its anti-fouling ability, extend its service life, and reduce maintenance costs. Common hydrophobic protection methods include:

[0004] Plasma surface treatment: Using high-energy particles in plasma to modify the surface of PVC, especially using fluorine-containing gas (such as CF4) for dielectric barrier discharge (DBD) treatment, can introduce fluorine elements on the surface of the material, significantly improving its hydrophobicity. At the same time, plasma treatment will cause slight etching of the material surface, increase the surface roughness, and further enhance the hydrophobic effect.

[0005] Chemical coating: Apply a hydrophobic coating (such as fluoride or silane coating) on ​​the surface of PVC to increase the hydrophobicity of the material by reducing the surface free energy. This type of coating can form a stable protective film and improve the corrosion resistance and weather resistance of the material.

[0006] Nanostructured surface design: Through micro-nanostructure processing technology (such as etching, printing, deposition, etc.), a nano-scale rough structure is constructed on the PVC surface to make it super hydrophobic. This technology simulates the microstructure of the lotus leaf surface in nature, so that water drops form spheres on the surface and slide down quickly, achieving a self-cleaning effect. However, the above hydrophobic protection method still has the following defects:

[0007] (1) Existing hydrophobic modification technologies (such as plasma treatment and chemical coating) are prone to cause the hydrophobic coating or surface modification layer to gradually fail during long-term use, especially under harsh environments such as ultraviolet rays, humidity, temperature changes, and mechanical friction, resulting in a decrease in hydrophobicity;

[0008] (2) Traditional hydrophobic coatings contain volatile organic compounds (VOCs) or perfluorinated and polyfluorinated substances (PFAS), which are potentially harmful to the environment and human body and are difficult to meet increasingly stringent environmental standards;

[0009] (3) Modification methods such as nanostructure design and high-energy plasma treatment require expensive equipment and complex processing, resulting in high costs for hydrophobic modification technology, which is not suitable for large-scale industrial applications;

[0010] (4) When modifying a large area of ​​PVC surface, the existing technology is difficult to ensure a uniform hydrophobic effect, especially on complex structures or irregular surfaces, where the thickness and uniformity of the modified layer may vary significantly;

[0011] (5) In the process of achieving super-hydrophobic modification, the surface roughness needs to be adjusted to obtain the best effect, but too high or too low roughness will affect the hydrophobic performance, and it is difficult to accurately control the roughness with existing technologies;

[0012] (6) Chemical coatings are easily affected by chemicals, moisture, etc. and become ineffective during long-term use, resulting in a decrease in the hydrophobicity of the material surface.

[0013] Therefore, how to provide a waterproof protection treatment method and application of cable sheath PVC material is a problem that needs to be solved urgently. Summary of the invention

[0014] The embodiment of the present invention provides a waterproof protection treatment method and application of a cable sheath PVC material to solve the problems of low durability and environmental protection in the prior art.

[0015] In order to have a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended to be a general review, nor is it intended to identify key / important components or to delineate the scope of protection of these embodiments. Its only purpose is to present some concepts in a simple form as a preface to the detailed description that follows.

[0016] According to a first aspect of an embodiment of the present invention, a method for waterproofing and protecting a cable sheath PVC material is provided.

[0017] In one embodiment, the cable sheath PVC material waterproof protection treatment method comprises:

[0018] Carbon tetrafluoride is used as a working gas for plasma discharge, a predefined plasma modification platform is used in combination with a dielectric barrier discharge technology to modify the polyvinyl chloride material to obtain a modified polyvinyl chloride material;

[0019] Conducting physical and chemical property tests on the modified polyvinyl chloride material to obtain the surface energy change state, and conducting a hydrophilic angle test on the modified polyvinyl chloride material based on the surface energy change state, and regulating the hydrophilicity of the polyvinyl chloride material according to the hydrophilic angle test results;

[0020] The pulse current decay technology is used to carry out pulse current decay test and breakdown voltage band test on the modified polyvinyl chloride material in turn, and the time-frequency domain dielectric properties of the polyvinyl chloride material are regulated by combining the pulse current decay test results and the breakdown voltage band test results.

[0021] In one embodiment, the plasma modification platform includes a gas path module, a circuit module and a modification experiment chamber module;

[0022] Among them, the gas circuit module is composed of a working gas cylinder, a flow meter, a pressure gauge and a vacuum pump; the circuit module is composed of an AC power supply, a high-voltage probe, a measuring resistor and an oscilloscope; and the modified experimental cavity module is composed of a modified cavity and a modified electrode.

[0023] In one embodiment, the AC power supply outputs a sine wave with a center frequency of 20 kHz; the high-voltage probe measures the voltage waveform of dielectric barrier discharge and is connected to the oscilloscope after the voltage waveform decays.

[0024] In one embodiment, the method of using carbon tetrafluoride as a working gas for plasma discharge, using a predefined plasma modification platform and combining dielectric barrier discharge technology to modify the polyvinyl chloride material to obtain the modified polyvinyl chloride material includes:

[0025] The pre-selected polyvinyl chloride material is laminated with the ceramic barrier medium. After the lamination is completed, the polyvinyl chloride material is placed on the ground electrode in the modified electrode, and another ceramic barrier medium is covered on the high-voltage electrode of the modified electrode, and the discharge spacing of the modified electrode is maintained within a preset range;

[0026] Connect the modified electrode to the electrical circuit, and verify whether the discharge spacing and electrical circuit connection of the modified electrode are correct, and proceed to the next step after the verification is completed;

[0027] The air pressure in the modified cavity is evacuated by a vacuum pump to a vacuum environment, and carbon tetrafluoride is filled into the modified cavity through a flow meter until the air pressure in the modified cavity reaches a preset range, and then a discharge test is performed;

[0028] The voltage of the resonant AC power supply is gradually increased within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrodes, and the discharge condition is observed to complete the plasma modification experiment and obtain the modified polyvinyl chloride material.

[0029] In one embodiment, the ceramic blocking medium is Al2O3 ceramic, the thickness of the Al2O3 ceramic is 1 mm, and the size of the Al2O3 ceramic is 100 mm×100 mm.

[0030] In one embodiment, the size of the Al2O3 ceramic covers the high voltage electrode and the ground electrode of the modified electrode, and the diameters of the high voltage electrode and the ground electrode are both 50 mm.

[0031] In one embodiment, the discharge spacing of the modified electrode is 4 mm.

[0032] In one embodiment, the flow rate of carbon tetrafluoride filled into the modification cavity through the flow meter is 0.2 L / min.

[0033] In one embodiment, the step of using a vacuum pump to evacuate the air in the modified cavity to a vacuum environment, and filling the modified cavity with carbon tetrafluoride through a flow meter until the air pressure in the modified cavity reaches a preset range, and then performing a discharge test includes:

[0034] Using a vacuum pump to initially evacuate the modified cavity, and judging whether the air pressure in the modified cavity is lower than a preset value, if the air pressure in the modified cavity is lower than the preset value, desorption is performed, otherwise, the vacuum pump is continuously evacuated;

[0035] After desorption, the modified cavity is evacuated again using a vacuum pump to determine whether the air pressure in the modified cavity is still lower than the preset value. If the air pressure in the modified cavity is still lower than the preset value, carbon tetrafluoride is filled into the modified cavity through a flow meter until the air pressure in the modified cavity reaches 1000Pa, and the discharge test is started. Otherwise, the vacuum pump is continuously evacuated.

[0036] In one embodiment, the step of gradually increasing the voltage of the resonant AC power supply within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrode and observing the discharge condition includes:

[0037] The voltage of the resonant AC power supply is gradually increased within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrode, and a voltage-current curve within the preset time period is obtained based on the voltage of the resonant AC power supply;

[0038] The voltage-current curve is integrated and calculated to obtain the power output power of the power supply during dielectric barrier discharge, and the discharge condition is analyzed based on the power output power.

[0039] In one embodiment, the pulse current amplitude of the voltage-current curve within the preset time period is up to 20 mA, and a number of discharge current pulses are present in the positive and negative half cycles.

[0040] In one embodiment, the calculation formula for the power output power during the dielectric barrier discharge is:

[0041]

[0042] Where M represents the length of the recorded data, Δt represents the sampling interval, and V n Represents the measured voltage, I n represents the measured current, n represents the number, T represents the test time, i represents the instantaneous current measured within the unit time t, dt represents the microelement, and E represents the electric field strength.

[0043] In one embodiment, the modified polyvinyl chloride material is subjected to a physical and chemical property test to obtain a surface energy change state, and the modified polyvinyl chloride material is subjected to a hydrophilic angle test based on the surface energy change state, and the hydrophilicity of the polyvinyl chloride material is adjusted according to the hydrophilic angle test result, including:

[0044] The surface energy change of the modified polyvinyl chloride material is tested, and the hydrophilic angle is used as a characterization basis to obtain the hydrophilic angle of the modified polyvinyl chloride material;

[0045] The modified polyvinyl chloride material is subjected to a photoelectron spectrum test, and a photoelectron spectrum curve is generated. The photoelectron spectrum line is subjected to peak calculation to obtain the content of each element on the surface of the modified polyvinyl chloride material.

[0046] Based on the chemical reaction mechanism of carbon tetrafluoride in plasma modification experiment, the chemical reaction between carbon tetrafluoride and polyvinyl chloride material is generated;

[0047] The chemical reaction between carbon tetrafluoride and polyvinyl chloride materials was analyzed, and the hydrophilicity of polyvinyl chloride materials was regulated in combination with the changes in the content of various surface elements and surface energy.

[0048] In one embodiment, the chemical reaction between carbon tetrafluoride and polyvinyl chloride material includes dissociation phenomenon, surface grafting phenomenon and decomposition phenomenon;

[0049] The dissociation phenomenon is a phenomenon in which the chemical bonds are broken due to the collision of free electrons in the chemical reaction between carbon tetrafluoride and polyvinyl chloride materials, and excited atoms or free radicals are generated.

[0050] The surface grafting phenomenon is that when the bond energy of the CH bond is less than the bond energy of the CF bond and the HF bond, the hydrogen radical in the free state will combine with the fluorine radical, and the carbon chain will combine with the remaining fluorine radicals;

[0051] The decomposition phenomenon is the desorption of carbon tetrafluoride in the plasma modification experiment, which leads to the decomposition of carbon tetrafluoride under long-term discharge conditions.

[0052] In one embodiment, the pulse current decay technology is used to sequentially perform a pulse current decay test and a breakdown voltage band test on the modified polyvinyl chloride material, and combined with the pulse current decay test results and the breakdown voltage band test results, the time-frequency domain dielectric properties of the polyvinyl chloride material are regulated, including:

[0053] The pulse current decay technology is used to perform a pulse current decay test on the modified polyvinyl chloride material to obtain a pulse current decay curve;

[0054] The relaxation time constant is obtained by performing spectrum analysis on the pulse current decay curve, and the relaxation time constant is input into the extended Debye model to obtain the trap depth corresponding to the relaxation time constant.

[0055] The DC conductivity and breakdown voltage of polyvinyl chloride materials are controlled based on the trap depth corresponding to the relaxation time constant;

[0056] The modified polyvinyl chloride material is subjected to a breakdown voltage band test to obtain the AC breakdown voltage of the polyvinyl chloride material before and after modification, and the bulk insulation of the polyvinyl chloride material is analyzed based on the AC breakdown voltage.

[0057] According to a second aspect of an embodiment of the present invention, an application of a method for waterproofing and protecting a cable sheath PVC material is provided.

[0058] In one embodiment, the cable sheath PVC material waterproof protection treatment method is used in the hydrophobic protection of polyvinyl chloride materials.

[0059] The technical solution provided by the embodiment of the present invention may have the following beneficial effects:

[0060] 1. The present invention uses CF4 plasma technology to fluorinate the surface of PVC, which effectively improves the hydrophobicity and weather resistance of PVC, so that the distribution of fluorine elements on the surface of PVC can be quickly adjusted, so that it increases rapidly in the initial stage of treatment, thereby achieving a significant hydrophobic effect in a relatively short time. Compared with the traditional chemical coating method, the present invention does not need to use additional chemical solvents, which is not only more environmentally friendly, but also can efficiently achieve the expected effect, and is very suitable for application scenarios with high environmental protection requirements.

[0061] 2. The present invention finds that the fluorine content shows a trend of "increasing first and then decreasing" by precisely controlling the processing time. At a specific time point, the fluorine content and the surface roughness reach the best match, thereby maximizing the hydrophobicity of the PVC surface. The present invention utilizes the dual effects of fluorination and etching of CF4 plasma, which not only increases the surface roughness, but also increases the surface fluorine content, thereby forming a "competitive effect" of enhancing hydrophobicity and weather resistance, thereby further extending the life of the modification effect.

[0062] 3. The present invention controls the change of the hydrophilic angle of the PVC surface with time by adjusting the DBD treatment time. Within a specific treatment time, the hydrophilic angle reaches a peak value, thereby obtaining the best hydrophobic performance. At the same time, in order to avoid performance degradation caused by excessive treatment, the CF4 decomposition process and its influence on the surface fluorination efficiency are monitored in real time, and the treatment time and gas flow rate are adjusted in time to ensure the optimization of the fluorination effect.

[0063] 4. The present invention verifies the modification effect through a variety of surface physical and chemical detection methods, comprehensively analyzes the surface fluorine content, roughness, hydrophilic angle and other properties, and provides accurate data support for process optimization. This systematic detection method can comprehensively evaluate the modification effect of PVC, provide reliable quality control methods for industrial applications, and quickly adjust the modification conditions to meet different needs.

[0064] 5. The present invention achieves a significant hydrophobic modification effect on the PVC surface through DBD treatment in a short time, which is suitable for industrial scenarios of rapid processing, so that the performance of the PVC surface can be effectively improved in a short time and production efficiency can be improved. At the same time, by dynamically monitoring the changes in the fluorine content, the parameters are automatically adjusted or the modification is terminated when the fluorine content begins to decrease to avoid over-treatment. The dynamic monitoring technology of the present invention ensures the stability of the fluorination treatment, avoids excessive etching or insufficient fluorine content, and thereby prolongs the retention time of the hydrophobic performance of the material.

[0065] 6. During the fluorination treatment process, the present invention achieves coordinated regulation of surface roughness and fluorine content by precisely controlling the etching intensity, thereby being able to adjust the hydrophilicity or hydrophobicity of the material surface as needed, allowing the PVC material to achieve diverse surface properties under the same modification process. This flexibility and versatility enable the method to meet the needs of different application scenarios, further broadening its scope of industrial application.

[0066] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0068] Figure 1 is a flow chart showing a method for waterproofing and protecting a cable sheath PVC material according to an exemplary embodiment;

[0069] Figure 2 It is a structural diagram of a DBD modification platform of CF4 in a method for waterproofing and protecting a cable sheath PVC material according to an exemplary embodiment;

[0070] Figure 3It is a schematic diagram of a CF4 plasma modification experiment process in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0071] Figure 4 It is a schematic diagram of DBD voltage and current waveforms during a PVC modification process in a method for waterproofing and protecting PVC material of a cable sheath according to an exemplary embodiment;

[0072] Figure 5 It is a discharge diagram when the surface of PVC material is modified in a method for waterproofing and protecting PVC material of a cable sheath according to an exemplary embodiment;

[0073] Figure 6 It is a schematic diagram of an emission spectrum when an externally applied voltage is 2.5 kV in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0074] Figure 7 is a hydrophilic angle diagram of an untreated PVC modified sample in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0075] Figure 8 It is a hydrophilic angle diagram of a PVC modified sample treated for 15 seconds in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0076] Fig. 9 It is a hydrophilic angle diagram of a PVC modified sample treated for 30 seconds in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0077] Fig.10 It is a hydrophilic angle diagram of a PVC modified sample treated for 60 seconds in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0078] Fig.11 It is a flow chart of processing 120s in a method for waterproofing and protecting PVC material of a cable sheath according to an exemplary embodiment;

[0079] Fig.12 It is a flow chart of processing 240s in a method for waterproofing and protecting PVC material of a cable sheath according to an exemplary embodiment;

[0080] Fig.13 It is a flow chart of processing 480s in a method for waterproofing and protecting PVC material of a cable sheath according to an exemplary embodiment;

[0081] Fig.14It is a schematic diagram of the hydrophilic angle test results of a PVC modified sample in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0082] Fig.15 It is an XPS spectrum of a PVC material before and after treatment for 120s in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0083] Fig.16 It is a comparison diagram of element contents of PVC at different modification times in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0084] Fig.17 is a schematic diagram of an untreated PVC sample in a method for waterproofing and protecting a cable sheath PVC material according to an exemplary embodiment;

[0085] Fig.18 This is a schematic diagram of a PVC sample after being treated for 120 seconds in a method for waterproofing and protecting a cable sheath PVC material according to an exemplary embodiment;

[0086] Fig.19 It is a three-branch relaxation time constant diagram of samples with different treatment times in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0087] Fig. 20 It is a three-branch trap depth diagram of a sample without treatment time in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0088] Fig.21 is a FDS curve diagram of PVC samples with different treatment times in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0089] Fig. 22 is a comparison diagram of tan δ of PVC samples at 0.1 Hz, 40 Hz and 70 Hz for different treatment times in a waterproof protection treatment method for a cable sheath PVC material according to an exemplary embodiment;

[0090] Fig.23 It is a diagram of an electrode structure of an AC withstand voltage test of a PVC sample in a method for waterproofing and protecting a PVC material for a cable sheath according to an exemplary embodiment;

[0091] Fig.24 It is an AC breakdown voltage of a PVC sample before and after DBD treatment in a method for waterproofing PVC material of a cable sheath according to an exemplary embodiment. DETAILED DESCRIPTION

[0092] The following description and accompanying drawings fully illustrate the specific embodiments of this article so that those skilled in the art can practice them. Parts and features of some embodiments may be included in or replace parts and features of other embodiments. The scope of the embodiments of this article includes the entire scope of the claims, as well as all available equivalents of the claims. Herein, the terms "first", "second", etc. are only used to distinguish one element from another, without requiring or implying any actual relationship or order between these elements. In fact, the first element can also be called the second element, and vice versa. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the structure, device or equipment including a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also include elements inherent to such structure, device or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the structure, device or equipment including the elements. Each embodiment is described in a progressive manner herein, and each embodiment focuses on the differences from other embodiments, and the same and similar parts between the embodiments can be referred to each other.

[0093] The terms "longitudinal", "lateral", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. in this document indicate the orientation or position relationship based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing this document and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of this document, unless otherwise specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a mechanical connection or an electrical connection, it can also be the internal communication of two elements, it can be a direct connection, or it can be an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0094] As used herein, the term "plurality" means two or more than two, unless otherwise specified.

[0095] In this document, the character " / " indicates that the preceding and following objects are in an "or" relationship. For example, A / B means: A or B.

[0096] In this article, the term "and / or" is a description of the association relationship between objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or, A and B.

[0097] It should be understood that, although the various steps in the flow chart are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear description in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a portion of the steps in the figure may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these sub-steps or stages is not necessarily to be carried out in sequence, but can be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.

[0098] Each module in the device or system of the present application can be implemented in whole or in part by software, hardware, or a combination thereof. The above modules can be embedded in or independent of a processor in a computer device in the form of hardware, or can be stored in a memory in a computer device in the form of software, so that the processor can call and execute operations corresponding to the above modules.

[0099] In the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0100] Figure 1 An embodiment of a waterproof protection treatment method for a cable sheath PVC material of the present invention is shown.

[0101] In this optional embodiment, the waterproof protection treatment method of the cable sheath PVC material includes:

[0102] Step S101, using carbon tetrafluoride as a working gas for plasma discharge, using a predefined plasma modification platform and combining dielectric barrier discharge technology to modify the polyvinyl chloride material to obtain a modified polyvinyl chloride material;

[0103] Step S103, performing a physical and chemical property test on the modified polyvinyl chloride material to obtain a surface energy change state, and performing a hydrophilic angle test on the modified polyvinyl chloride material based on the surface energy change state, and adjusting the hydrophilicity of the polyvinyl chloride material according to the hydrophilic angle test result;

[0104] Step S105, using pulse current decay technology to perform pulse current decay test and breakdown voltage band test on the modified polyvinyl chloride material in sequence, and combining the pulse current decay test results and the breakdown voltage band test results to adjust the time-frequency domain dielectric properties of the polyvinyl chloride material.

[0105] In this optional embodiment, the plasma modification platform includes a gas circuit module, a circuit module and a modified experimental chamber module; wherein the gas circuit module is composed of a working gas cylinder, a flow meter, a pressure gauge and a vacuum pump; the circuit module is composed of an AC power supply, a high-voltage probe, a measuring resistor and an oscilloscope; and the modified experimental chamber module is composed of a modified chamber and a modified electrode.

[0106] In this optional embodiment, the AC power supply outputs a sine wave with a center frequency of 20 kHz; the high-voltage probe measures the voltage waveform of the dielectric barrier discharge and is connected to the oscilloscope after the voltage waveform decays.

[0107] In this optional embodiment, the method of using carbon tetrafluoride as the working gas for plasma discharge, using a predefined plasma modification platform and combining dielectric barrier discharge technology to modify the polyvinyl chloride material to obtain the modified polyvinyl chloride material includes:

[0108] The pre-selected polyvinyl chloride material is bonded to the ceramic barrier medium. After the bonding is completed, the polyvinyl chloride material is placed on the ground electrode in the modified electrode, and another ceramic barrier medium is covered on the high-voltage electrode of the modified electrode, and the discharge spacing of the modified electrode is maintained within a preset range; the modified electrode is electrically connected, and the discharge spacing and electrical circuit connection of the modified electrode are verified to be correct, and the next step is performed after the verification is completed; the air pressure in the modified cavity is evacuated by a vacuum pump to reach a vacuum environment, and carbon tetrafluoride is filled into the modified cavity through a flow meter until the air pressure in the modified cavity reaches a preset range and a discharge test is performed; the voltage of the resonant AC power supply is gradually increased within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier media on the modified electrode, and the discharge condition is observed to complete the plasma modification experiment and obtain the modified polyvinyl chloride material.

[0109] In this optional embodiment, the ceramic blocking medium is Al2O3 ceramic, the thickness of the Al2O3 ceramic is 1 mm, and the size of the Al2O3 ceramic is 100 mm×100 mm.

[0110] In this optional embodiment, the size of the Al2O3 ceramic covers the high voltage electrode and the ground electrode of the modified electrode, and the diameters of the high voltage electrode and the ground electrode are both 50 mm.

[0111] In this optional embodiment, the discharge spacing of the modified electrodes is 4 mm.

[0112] In this optional embodiment, the flow rate of carbon tetrafluoride filled into the modification cavity through the flow meter is 0.2 L / min.

[0113] In this optional embodiment, the step of using a vacuum pump to evacuate the air pressure in the modified cavity to a vacuum environment, and filling the modified cavity with carbon tetrafluoride through a flow meter until the air pressure in the modified cavity reaches a preset range, and then performing a discharge test includes:

[0114] Use a vacuum pump to initially evacuate the modified cavity, and determine whether the air pressure in the modified cavity is lower than the preset value. If the air pressure in the modified cavity is lower than the preset value, desorption is performed; otherwise, the vacuum pump is continuously evacuated. After desorption, use a vacuum pump to evacuate the modified cavity again, and determine whether the air pressure in the modified cavity is still lower than the preset value. If the air pressure in the modified cavity is still lower than the preset value, carbon tetrafluoride is filled into the modified cavity through a flow meter until the air pressure in the modified cavity reaches 1000Pa, and the discharge test is started; otherwise, the vacuum pump is continuously evacuated.

[0115] In this optional embodiment, gradually increasing the voltage of the resonant AC power supply within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrode and observing the discharge condition includes:

[0116] The voltage of the resonant AC power supply is gradually increased within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrode, and a voltage-current curve within the preset time period is obtained based on the voltage of the resonant AC power supply; the voltage-current curve is integrated and calculated to obtain the power supply output power during dielectric barrier discharge, and the discharge condition is analyzed based on the power supply output power.

[0117] In this optional embodiment, the pulse current amplitude of the voltage-current curve within the preset time period is up to 20 mA, and a number of discharge current pulses are present in the positive and negative half cycles.

[0118] In this optional embodiment, the modified polyvinyl chloride material is subjected to a physical and chemical property test to obtain a surface energy change state, and the modified polyvinyl chloride material is subjected to a hydrophilic angle test based on the surface energy change state, and the hydrophilicity of the polyvinyl chloride material is adjusted according to the hydrophilic angle test result, including:

[0119] The surface energy change of the modified polyvinyl chloride material is tested, and the hydrophilic angle is used as the characterization basis to obtain the hydrophilic angle of the modified polyvinyl chloride material; the modified polyvinyl chloride material is tested by photoelectron energy spectrum, and a photoelectron energy spectrum curve is generated, and the peak calculation of the photoelectron energy spectrum line is performed to obtain the content of each surface element of the modified polyvinyl chloride material; based on the chemical reaction mechanism of carbon tetrafluoride under plasma modification experiment, the chemical reaction of carbon tetrafluoride and polyvinyl chloride material is generated; the chemical reaction of carbon tetrafluoride and polyvinyl chloride material is analyzed, and the hydrophilicity of the polyvinyl chloride material is regulated in combination with the content of each surface element and the change of surface energy.

[0120] In this optional embodiment, the chemical reaction between carbon tetrafluoride and polyvinyl chloride material includes dissociation phenomenon, surface grafting phenomenon and decomposition phenomenon;

[0121] Among them, the dissociation phenomenon is the phenomenon that in the chemical reaction between carbon tetrafluoride and polyvinyl chloride materials, the chemical bonds are broken due to the collision of free electrons and excited atoms or free radicals are generated; the surface grafting phenomenon is the phenomenon that when the bond energy of the CH bond is less than the bond energy of the CF bond and the HF bond, the hydrogen radicals in the free state will combine with the fluorine radicals, and the carbon chain will combine with the remaining fluorine radicals; the decomposition phenomenon is the desorption of carbon tetrafluoride under the plasma modification experiment, which leads to the decomposition of carbon tetrafluoride under long-term discharge conditions.

[0122] In this optional embodiment, the pulse current decay technology is used to sequentially perform a pulse current decay test and a breakdown voltage band test on the modified polyvinyl chloride material, and combined with the pulse current decay test results and the breakdown voltage band test results, the time-frequency domain dielectric properties of the polyvinyl chloride material are regulated, including:

[0123] The modified polyvinyl chloride material is subjected to a pulse current decay test using the pulse current decay technology to obtain a pulse current decay curve; the pulse current decay curve is subjected to spectral analysis to obtain a relaxation time constant, and the relaxation time constant is input into the extended Debye model to obtain a trap depth corresponding to the relaxation time constant; the DC conductivity and breakdown voltage of the polyvinyl chloride material are controlled based on the trap depth corresponding to the relaxation time constant; a breakdown voltage band test is performed on the modified polyvinyl chloride material to obtain the AC breakdown voltage of the polyvinyl chloride material before and after modification, and the bulk insulation of the polyvinyl chloride material is analyzed based on the AC breakdown voltage.

[0124] In order to facilitate understanding of the above technical solution of the present invention, the waterproof protection treatment method of the cable sheath PVC material in the actual process of the present invention is described in detail below.

[0125] CF4 (carbon tetrafluoride) plasma modification platform:

[0126] For PVC material (Polyvinyl Chloride, PVC, i.e. polyvinyl chloride material), it is a kind of high molecular material with excellent performance and wide application, and it has become one of the commonly used plastics in modern industry and daily life because of its excellent mechanical properties, low price and easy processing) and has the deterioration caused by moisture, the present invention considers using the method of discharge plasma to improve its material hydrophobicity, and it is expected to further improve its dielectric response characteristics. At present, the classical plasma modification method mainly includes atmospheric pressure plasma jet (Atmospheric Pressure Plasma Jet, APPJ) and dielectric barrier discharge (Dielectric Barrier Discharge, DBD) two types of methods, which have the advantages of good effect, low cost and less waste materials relative to traditional methods, and therefore have relatively extensive research and application at home and abroad. At the same time, due to the expectation of improving the dielectric response characteristics of the material by improving the material trap depth, it is considered to introduce the fluorine element with strong electronegativity in PVC, and CF4 is used as the working fluid gas of plasma discharge.

[0127] In order to improve the processing uniformity, the present invention uses CF4 DBD (Dielectric Barrier Discharge) to modify the PVC material and builds a plasma modification platform, such as Figure 2 shown.

[0128] The entire modification platform is mainly divided into three parts: gas circuit, circuit and modified experimental chamber. The gas circuit part mainly includes working gas cylinder, flow meter, pressure gauge and vacuum pump; the circuit part mainly includes AC power supply, high voltage probe, measuring resistor R and oscilloscope; the modified experimental chamber part mainly includes chamber and DBD discharge electrode.

[0129] Since pure CF4 plasma modification is required under low pressure, the vacuum chamber must be sufficiently airtight and the vacuum pump must be able to pump to 0.1Pa or below. Two high-voltage bushings are reserved in the vacuum chamber for wiring of high-voltage and ground electrodes. The bushing material is polytetrafluoroethylene, and a quartz glass observation window is reserved to facilitate the observation of discharge uniformity. Since the plasma discharge voltage varies greatly under low pressure, the resolution of the barometer is required to be 0.1Pa to ensure that the pressure is consistent in each experiment. The resonant AC power supply (Nanjing Suman CTP-2000KSP) used can output a sine wave with a center frequency of 20kHz. The high-voltage probe (Tektronix P6015A) can effectively measure the voltage waveform of DBD discharge. After attenuation 1000 times (bandwidth 75MHz), it is connected to an oscilloscope (LeCroy waveSurfer104MXs-B). The oscilloscope also characterizes the corresponding current waveform by measuring the voltage across a 75Ω non-inductive resistor. In order to study the optical characteristics of DBD during discharge, a camera device was used to record the discharge image, and a step grating spectrometer was used to collect the spectrum during the discharge process.

[0130] In the DBD discharge modification area, in order to ensure that the discharge is as uniform as possible, parallel plate electrodes are used, and the diameter of the electrode is much larger than the spacing of the gap. The barrier medium used is Al2O3 ceramic with a thickness of 1mm. In order to prevent the plasma discharge from bypassing the barrier medium when the barrier medium size is too small and forming an arc discharge that penetrates the two electrodes, the Al2O3 ceramic size needs to cover the high-voltage electrode and the ground electrode (the diameter of both electrodes is 50mm), so the medium size currently selected is 100mm×100mm. The PVC sample is required to fit tightly with the Al2O3 ceramic barrier medium covering the ground electrode without air gaps, and the thickness is 200μm.

[0131] PVC plasma modification process:

[0132] The PVC plasma modification process adopted by the present invention is as follows Figure 3 The PVC sample and the Al2O3 ceramic barrier medium need to fit tightly together. In order to prevent the two from being misaligned or not fitting tightly during movement, which may affect the discharge efficiency, the PVC sample will be directly pasted on the Al2O3 ceramic barrier medium in actual operation.

[0133] After the bonding is completed, the PVC sample can be placed on the ground electrode in the modified electrode, and at the same time, another Al2O3 ceramic barrier medium is also covered on the high-voltage electrode. When placing, the DBD discharge area spacing between the upper and lower barrier media is required to be 4mm, and the two barrier media must be aligned. After completion, the entire modified electrode is placed steadily in the vacuum chamber. After the movement is completed, it is necessary to check again whether the spacing of the DBD discharge area is still 4mm and whether the barrier media covering the two electrodes are aligned.

[0134] When wiring the electrical wires, please note that due to the high voltage of the leads, to prevent discharge to the cavity and other objects, the leads must be short and hard. Any part of the leads cannot be connected to the cavity or other metal objects. If the leads are too long, it is recommended to use insulating materials such as polytetrafluoroethylene and epoxy resin to isolate the potential.

[0135] After the modified electrode discharge spacing is confirmed and the electrical circuit connection is completed, the vacuum pump can be turned on to evacuate the air pressure in the vacuum chamber to a vacuum. Due to the range limitation of the barometer, it is generally believed that the air pressure in the chamber is lower than 0.1Pa, which can be regarded as a vacuum. During the evacuation process, the evacuation port, the air filling port, the barometer and other interfaces need to be opened and closed several times to exhaust the air that may exist at the above interfaces (usually around 100Pa). After the first evacuation to make the air pressure in the chamber lower than 0.1Pa, the evacuation port valve must be closed before the vacuum pump is turned off to prevent the outside air from flowing back into the chamber.

[0136] After the first vacuuming is completed, the entire cavity needs to be left still for a period of time so that the electrodes, materials, and cavity walls in the vacuum cavity have enough time to desorb the gas. Since organic materials generally adsorb more gas than inorganic materials and metals, the desorption time needs to be determined according to the volume of the organic material. Since the thickness and overall volume of the organic material used in the present invention are relatively small, the desorption time is set to 15 minutes. After the gas desorption is completed, it is necessary to vacuum again. At this time, the vacuum pump must be turned on first, and then the valve of the vacuum port must be opened, otherwise air backflow may also occur.

[0137] After ensuring the vacuum environment in the cavity, the flow meter can be turned on to fill the cavity with pure CF4 (purity is 99.9999%), and the gas flow rate is controlled to 0.2L / min until the pressure in the cavity reaches 1000Pa. Since CF4 is corrosive to a certain extent and can etch the observation window, the discharge experiment should be carried out as soon as possible after the filling is completed.

[0138] When starting the discharge experiment, the operator needs to gradually increase the voltage of the resonant AC power supply until a uniform DBD discharge phenomenon appears in the gap between the upper and lower media. During this process, the environment needs to be kept dark in order to observe the discharge and start timing quickly. While ensuring that the modified electrode does not discharge to the cavity wall, the modified voltage should be increased as much as possible. At present, the highest modified voltage in this experiment is Vp-p=2.9kV, and the generally used modified voltage is 2.5kV.

[0139] When changing samples, gloves must be worn to prevent contamination of the sample surface, and the processed samples must be placed in a plastic bag in a timely manner. After all samples are processed, air must be introduced and evacuated several times to prevent the residual CF4 gas from corrosive to the gas path and cavity.

[0140] The electrical and optical properties of PVC during modification mainly include its current and voltage waveforms, discharge images and emission spectra, as shown in Figure 4-Figure 6 As shown. In a pure CF4 gas atmosphere, the discharge current waveform of the DBD shows obvious periodicity, and the maximum pulse current amplitude is about 20mA. Multiple discharge current pulses are presented in both the positive and negative half-cycles, and the amplitude of the negative pulse is relatively high. From the discharge time, the first pulse current of the positive and negative discharges lags behind the corresponding AC voltage zero crossing point by 0.9μs, indicating that the corresponding DBD gap breakdown field strength under the positive and negative polarities is basically the same, and the discharge area shows the characteristics of a uniform electric field.

[0141] In order to determine the power output power of the power supply during DBD discharge, the present invention adopts the voltage-current-time integration definition method to obtain the average power. The power calculation is mainly divided into two steps: first, integrate the voltage-current curve for a period of time, and then divide it by the corresponding integration time. The calculation formula is:

[0142]

[0143] Where M represents the length of the recorded data, Δt represents the sampling interval, and V n Represents the measured voltage, I n represents the measured current, n represents the number, T represents the test time, i represents the instantaneous current measured within the unit time t, dt represents the microelement, and E represents the electric field strength.

[0144] Since there is capacitive reactive power during DBD discharge, in order to eliminate the impact of reactive power on the average power result, the test time T must be several complete cycles. Combined with the output voltage, the output power during discharge is 1.68W.

[0145] In the experiment, the exposure time of the digital camera was manually set to 1 / 5s, the ISO value was 2000; the single exposure time of the spectral imaging was set to 5s, the gain was 4095 times, the gate width time was 0.5s, the accumulation mode was used, and the cumulative number of times was 100. When collecting the discharge spectrum, the temperature in the cavity was 23℃ and the relative humidity was 32%.

[0146] like Figure 5 As shown, the discharge area appears purple-red and has a relatively consistent and stable shape, which is a typical uniform discharge shape. This can effectively improve the consistency of the DBD discharge treatment sample results. Figure 6 The emission spectrum of CF4 DBD at an applied voltage of 2.5 kV is shown, and the emission spectrum ranges from 200 to 900 nm. The peak of the continuous spectrum at around 620 nm is caused by CF3 free radicals, which are produced by the excitation of high-energy free electrons. CF3 free radicals are generally considered to be a transition product, which gradually converts into CF2 and F as the treatment time goes by. The peak of the continuous spectrum at around 290 nm is related to CF2, CF4 and their free radicals, while the continuous spectrum at around 700 to 750 nm is considered to be related to F and its free radicals. The detailed reaction process will be further analyzed in the subsequent content. It is worth noting that since the accumulation mode is used when the spectrum is taken, the total shooting time is about 500 s, so the samples in the electrode, blocking medium and sample to be treated will inevitably desorb N2, resulting in a relatively obvious N2 spectrum line.

[0147] Physical and chemical properties testing and analysis of modified materials:

[0148] According to the CF4 plasma modification method, the PVC samples were modified for 15s, 30s, 60s, 120s, 240s and 480s respectively. After the modification, in order to investigate the changes in the chemical elements and surface morphology of the material, the surface energy, X-ray photoelectron spectroscopy (XPS) and scanning electron microscope (SEM) were performed. First, the changes in the surface energy of the material were tested, and the hydrophilic angle was used as the characterization basis. The measured hydrophilic angle of the PVC modified sample is as follows: Figure 7-Figure 13 At the same time, in order to study the effect attenuation of the modified PVC after being placed for a period of time, a hydrophilic angle test was conducted on it again. The results of the two tests were compared. Fig.14 shown.

[0149] From the current results, it can be seen that with the increase of treatment time, the hydrophilic angle of PVC shows a trend of first rising and then falling, obtaining hydrophobicity similar to that of polytetrafluoroethylene. When the treatment time is longer, the hydrophilicity of the cable increases significantly, even better than the initial hydrophilicity of PVC material. After a period of time of CF4 treatment, the hydrophilic angle test effect has declined, but it still has a more obvious modification effect than the untreated PVC.

[0150] As shown in Table 1, polyethylene was plasma fluorinated using CF4. From the results, it can be seen that after a short-term treatment, there is indeed a similar situation of first increasing and then decreasing, which is similar to the results of the present invention; but the decrease is not obvious under long-term treatment.

[0151] Table 1 Effect of plasma glow discharge on the hydrophilic angle of PVC after modification

[0152]

[0153]

[0154] The reason for this phenomenon is that the surface energy of the material is mainly determined by its morphological characteristics and chemical components. There is a competitive relationship between the two. Therefore, the surface elements / chemical bonds and morphological changes were analyzed. First, XPS tests were performed on PVC with different treatment times. The typical XPS spectra of untreated and treated PVC samples are shown in Figure 2. Fig.15 shown.

[0155] from Fig.15 It can be found that the treated PVC has obvious peaks of F1s and FKLL, which also proves that the fluorine element forms a CF bond with the carbon chain of PVC. According to the XPS spectra of PVC samples with different treatment times, the content of each element is obtained by peak calculation, such as Fig.16 shown.

[0156] from Fig.16 It can be seen from the results that the change trend of the fluorine content is similar to the hydrophilic angle test results, and it also shows a trend of first increasing and then decreasing. The two show a certain correlation. Therefore, the fluorine element and its functional groups can effectively reduce the surface energy of PVC.

[0157] In order to more accurately reflect the changes in chemical bonds during the treatment process, the obtained C1s spectrum was further peak-separated, and the results are shown in Table 2. From the results of chemical bond analysis, it can be seen that the untreated PVC sample mainly contains CC and CO bonds. Among them, the CO bond, in addition to mainly coming from the oxidation byproducts during the cross-linking process, may also come from the oxygen adsorption in the air. After DBD surface treatment, the CO bond has been significantly reduced, while the content of CC, CF, CF-CF2 and CF3 bonds has increased. However, this phenomenon changes with the extension of DBD treatment time. When the treatment time is greater than 120s, the content of CO bonds will begin to increase again, while the content of other chemical bonds will begin to decrease, which is similar to the trend of the content change of the F element.

[0158] Table 2 Results of chemical bond content based on C1s

[0159]

[0160] Combining Table 2 with the chemical reaction process of CF4 under plasma, and considering that many high-energy free electrons will be generated during the DBD treatment, the chemical reaction of CF4 and PVC can be mainly divided into three parts: dissociation / excitation, surface grafting and decomposition.

[0161] During the dissociation / excitation process, chemical bonds are broken due to collisions with free electrons, generating excited atoms or free radicals, as shown below.

[0162] In gas:

[0163]

[0164] On the surface:

[0165]

[0166] Here, R represents the carbon chain. Since the bond energy of the CH bond (414.2 kJ / mol) is smaller than the bond energy of the CF bond (485.3 kJ / mol) and the HF bond (568.2 kJ / mol), the hydrogen radicals in the free state will combine with the fluorine radicals instead of the carbon chain. At this time, the carbon chain will combine with other fluorine radicals. This is also called the surface grafting phenomenon, as shown below.

[0167] R·+F·→RF

[0168] H·+F·→HF

[0169] Although the DBD modification of CF4 was performed with at least 15 minutes of gas desorption preparation before the experiment, some air was inevitably left behind and continued to desorb during the experiment. At the same time, CF4 will decompose under long-term discharge conditions, and its intermediate products can react with oxygen, as shown below.

[0170]

[0171] O·+CF3·→COF2+F

[0172] O·+CF2→COF+F·

[0173] O·+COF→CO2+F·

[0174] It can be found that a lot of fluorine free radicals are newly generated during the reaction. In addition to the continued grafting reaction, other substances may also be produced. After a long period of modification, a more obvious irritating gas can be smelled in the vacuum chamber when sampling, and a small amount of white smoke will appear when the humidity is high. Since CF4 is a colorless and odorless gas, the above gas should be a by-product produced after the reaction. According to existing literature reports, this irritating gas is SiF4. The reason for the generation of this by-product is: in order to observe the discharge form, the CF4 experimental chamber will reserve an observation window made of silicon dioxide material, and fluorine free radicals can react with silicon dioxide, as shown below:

[0175] SiO2+4F→SiF4+2O

[0176] Since the bond energy of Si-F bond (565 kJ / mol) and HF bond is higher than that of CF bond, DBD plasma treatment for too long will cause CF bond to be converted into Si-F and HF bond, thus affecting the modification efficiency.

[0177] As mentioned above, the surface morphology will also affect the performance of the material. In order to compare the morphological characteristics of PVC before and after treatment, the present invention compares the SEM images of the untreated sample and the sample treated for 240s. Figure 17-Figure 18 shown.

[0178] from Figure 17-Figure 18 It can be seen that the treated PVC samples have more grooves and are rougher than the untreated PVC samples. According to Wenzel theory, when the initial hydrophilic angle of the material is less than 90°, the hydrophilic angle will decrease as the surface roughness increases. Therefore, the hydrophilicity of the material can be effectively controlled by combining the changes in fluorine content and material roughness.

[0179] Time-frequency domain dielectric response and breakdown voltage analysis of modified PVC materials:

[0180] In terms of the time domain dielectric properties of the modified PVC, the PDC method was mainly used for the corresponding testing, diagnosis and analysis. After the PDC test on the modified sample, the extended Debye model in the prior art was used to analyze the measured PDC curve, and the three-branch relaxation time constant results of the sample at different processing times were obtained, such as Fig.19 It should be noted that the standard deviations of bulk polarization and grain boundary polarization are relatively small, so they are not as obvious as impurity interface polarization in the figure.

[0181] Substituting the relaxation time constants of the three branches into the extended Debye model, the trap depths corresponding to the three different polarization types can be obtained, such as Fig. 20 shown.

[0182] from Fig.19 and Fig. 20 It can be seen that the relaxation time constant and trap depth of bulk polarization remain basically unchanged, while the grain boundary polarization and impurity interface polarization show a trend of first increasing and then decreasing, which is similar to the test results of hydrophilic angle and fluorine content. From the experimental results, it can be found that DBD modification treatment cannot affect the bulk polarization process. Referring to Strobel's point of view, since fluorine and its free radicals are mainly connected to the carbon chain through grafting, they mainly affect the grain boundary and impurity interface polarization of PVC. At the same time, due to the strong electronegativity of fluorine, when the fluorine content increases, the overall electron capture ability of the material can be improved and the trap depth can be increased. The captured electrons can further weaken the external electric field, so that the subsequent charge injection ability is suppressed. This trap characteristic is also often used to improve the DC conductivity and breakdown voltage of the material.

[0183] In terms of the frequency domain dielectric properties of PVC materials, the FDS curve is mainly used for targeted analysis. The FDS curve of the modified PVC material is as follows: Fig.21 As shown. Fig.21 It can be seen that the FDS curve of the modified PVC sample is significantly lower than that of the unmodified PVC sample in the low frequency band. Since the low-frequency dielectric loss value of the FDS curve is mainly determined by the DC conductivity of the material, this also proves that the DC conductivity of the modified PVC sample has been significantly improved, which is consistent with the results obtained in the time domain.

[0184] In order to clarify the dielectric loss variation trend of the material at the key frequency points, the dielectric loss of samples with different processing times at 0.1Hz, 40Hz and 70Hz were collected, such as Fig. 22 This is because the operating frequency of the mainstream power grid is 50Hz or 60Hz. When conducting dielectric loss test, it is necessary to avoid these two frequency points to avoid interference, so 40Hz or 70Hz is selected instead. At the same time, if the capacitance of the equipment to be tested on site is too large, the frequency is often reduced to meet the test requirements. At this time, the dielectric loss test at 0.1Hz is the most widely used.

[0185] from Fig. 22 It can be seen that the dielectric loss of each sample at these three frequency points shows a trend of first decreasing and then increasing with the extension of processing time, which is exactly the opposite of the results of hydrophilic angle test, fluorine content and trap depth test, but all represent the improvement of the insulation performance of the material.

[0186] Among them, the material dielectric loss is the lowest when DBD is treated for 240s at 0.1Hz. Since the dielectric loss at low frequency (0.1Hz) is mainly determined by the conductivity of the material, the conductivity of the PVC material reaches the lowest after 240s of treatment. The reason for this is that as the trap depth of the material increases, the material can inject more carriers, weakening the external electric field while reducing the carrier mobility, making the material's conductivity reach the lowest.

[0187] The material dielectric loss is the lowest when DBD is treated for 120s at 40 and 70Hz, which is the result of the combined effect of material conductivity and polarization process. Although the trap depth of the sample treated for 120s is not the deepest, its fluorine content is the highest. A higher fluorine content can reduce the relative dielectric constant and the corresponding polarization process, and finally the tanδ value is minimized under the action of the conductivity process.

[0188] In order to more intuitively verify the insulation state of the modified PVC material, the present invention conducted AC withstand voltage tests on the PVC material before and after modification. The breakdown used a spherical electrode with a diameter of 25 mm. The electrode support was epoxy resin. The electrode structure was as follows: Fig.23 As shown. In order to prevent surface discharge of the film during the withstand voltage test, the electrode needs to be immersed in transformer oil as a whole. Since the breakdown voltage of the material in the withstand voltage test is dispersed, each processed sample needs to be tested 5 to 10 times.

[0189] The AC breakdown voltage results of PVC samples before and after treatment are as follows: Fig.24 As shown in the results, it can be seen that with the increase of modification time, the breakdown voltage of the material also shows a trend of first increasing and then decreasing. This result is consistent with the aforementioned law and analysis of the change of trap depth, proving that the bulk insulation performance of the treated PVC material is indeed improved.

[0190] Combined with the changing patterns of hydrophilic angle, fluorine content, trap depth, dielectric loss and AC breakdown voltage, relatively ideal results can be obtained when DBD treatment is performed for 120s or 240s.

[0191] The present invention is not limited to the structures which have been described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A method for waterproofing and protecting cable sheath PVC material, characterized in that: include: Carbon tetrafluoride is used as a working gas for plasma discharge, and a predefined plasma modification platform is used in combination with a dielectric barrier discharge technology to modify the polyvinyl chloride material to obtain a modified polyvinyl chloride material; Conducting physical and chemical property tests on the modified polyvinyl chloride material to obtain a surface energy change state, and conducting a hydrophilic angle test on the modified polyvinyl chloride material based on the surface energy change state, and regulating the hydrophilicity of the polyvinyl chloride material according to the hydrophilic angle test results; The pulse current decay technology is used to carry out pulse current decay test and breakdown voltage band test on the modified polyvinyl chloride material in turn, and the time-frequency domain dielectric properties of the polyvinyl chloride material are regulated by combining the pulse current decay test results and the breakdown voltage band test results.

2. The waterproof protection treatment method for cable sheath PVC material according to claim 1 is characterized in that: The plasma modification platform includes a gas path module, a circuit module and a modification experiment chamber module; Among them, the gas circuit module is composed of a working gas cylinder, a flow meter, a pressure gauge and a vacuum pump; the circuit module is composed of an AC power supply, a high-voltage probe, a measuring resistor and an oscilloscope; and the modified experimental cavity module is composed of a modified cavity and a modified electrode.

3. The waterproof protection treatment method for cable sheath PVC material according to claim 2 is characterized in that: The AC power supply outputs a sine wave with a center frequency of 20 kHz; the high-voltage probe measures the voltage waveform of dielectric barrier discharge and is connected to the oscilloscope after the voltage waveform decays.

4. The waterproof protection treatment method for cable sheath PVC material according to claim 3 is characterized in that: The modified polyvinyl chloride material obtained by using carbon tetrafluoride as the working gas of plasma discharge and using a predefined plasma modification platform in combination with a dielectric barrier discharge technology comprises: The pre-selected polyvinyl chloride material is laminated with the ceramic barrier medium. After the lamination is completed, the polyvinyl chloride material is placed on the ground electrode in the modified electrode, and another ceramic barrier medium is covered on the high-voltage electrode of the modified electrode, and the discharge spacing of the modified electrode is maintained within a preset range; Connect the modified electrode to the electrical circuit, and verify whether the discharge spacing and electrical circuit connection of the modified electrode are correct, and proceed to the next step after the verification is completed; The air pressure in the modified cavity is evacuated by a vacuum pump to a vacuum environment, and carbon tetrafluoride is filled into the modified cavity through a flow meter until the air pressure in the modified cavity reaches a preset range, and then a discharge test is performed; The voltage of the resonant AC power supply is gradually increased within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrodes, and the discharge condition is observed to complete the plasma modification experiment and obtain the modified polyvinyl chloride material.

5. The waterproof protection treatment method for cable sheath PVC material according to claim 4 is characterized in that: The ceramic barrier medium is Al2O3 ceramic, the thickness of the Al2O3 ceramic is 1 mm, and the size of the Al2O3 ceramic is 100 mm×100 mm.

6. The waterproof protection treatment method for cable sheath PVC material according to claim 5, characterized in that: The size of the Al2O3 ceramic covers the high-voltage electrode and the ground electrode of the modified electrode, and the diameters of the high-voltage electrode and the ground electrode are both 50 mm.

7. The waterproof protection treatment method for cable sheath PVC material according to claim 6, characterized in that: The discharge spacing of the modified electrode is 4 mm.

8. The waterproof protection treatment method for cable sheath PVC material according to claim 7, characterized in that: The flow rate of carbon tetrafluoride filled into the modified cavity by the flow meter is 0.2 L / min.

9. The waterproof protection treatment method for cable sheath PVC material according to claim 8, characterized in that: The method of using a vacuum pump to evacuate air so that the air pressure in the modified cavity reaches a vacuum environment, and filling the modified cavity with carbon tetrafluoride through a flow meter until the air pressure in the modified cavity reaches a preset range, and then performing a discharge test includes: Using a vacuum pump to initially evacuate the modified cavity, and judging whether the air pressure in the modified cavity is lower than a preset value, if the air pressure in the modified cavity is lower than the preset value, desorption is performed, otherwise, the vacuum pump is continuously evacuated; After desorption, the modified cavity is evacuated again using a vacuum pump to determine whether the air pressure in the modified cavity is still lower than the preset value. If the air pressure in the modified cavity is still lower than the preset value, carbon tetrafluoride is filled into the modified cavity through a flow meter until the air pressure in the modified cavity reaches 1000Pa, and the discharge test is started. Otherwise, the vacuum pump is continuously evacuated.

10. The waterproof protection treatment method for cable sheath PVC material according to claim 9, characterized in that: The step of gradually increasing the voltage of the resonant AC power supply within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrode and observing the discharge condition comprises: The voltage of the resonant AC power supply is gradually increased within a preset time period until a dielectric barrier discharge phenomenon occurs in the gap between the ceramic barrier dielectrics on the modified electrode, and a voltage-current curve within the preset time period is obtained based on the voltage of the resonant AC power supply; The voltage-current curve is integrated and calculated to obtain the power output power of the power supply during dielectric barrier discharge, and the discharge condition is analyzed based on the power output power.

11. The waterproof protection treatment method for cable sheath PVC material according to claim 10, characterized in that: The pulse current amplitude of the voltage-current curve within the preset time period is up to 20 mA, and a number of discharge current pulses are present in the positive and negative half cycles.

12. The waterproof protection treatment method for cable sheath PVC material according to claim 11, characterized in that: The calculation formula of the power supply output power during the dielectric barrier discharge is: Where M represents the length of the recorded data, Δt represents the sampling interval, and V n Represents the measured voltage, I n represents the measured current, n represents the number, T represents the test time, i represents the instantaneous current measured within the unit time t, dt represents the microelement, and E represents the electric field strength.

13. The waterproof protection treatment method for cable sheath PVC material according to claim 12, characterized in that: The modified polyvinyl chloride material is subjected to a physical and chemical property test to obtain a surface energy change state, and the modified polyvinyl chloride material is subjected to a hydrophilic angle test based on the surface energy change state, and the hydrophilicity of the polyvinyl chloride material is adjusted according to the hydrophilic angle test result, including: The surface energy change of the modified polyvinyl chloride material is tested, and the hydrophilic angle is used as a characterization basis to obtain the hydrophilic angle of the modified polyvinyl chloride material; The modified polyvinyl chloride material is subjected to a photoelectron spectrum test, and a photoelectron spectrum curve is generated. The photoelectron spectrum line is subjected to peak calculation to obtain the content of each element on the surface of the modified polyvinyl chloride material. Based on the chemical reaction mechanism of carbon tetrafluoride in plasma modification experiment, the chemical reaction between carbon tetrafluoride and polyvinyl chloride material is generated; The chemical reaction between carbon tetrafluoride and polyvinyl chloride materials was analyzed, and the hydrophilicity of polyvinyl chloride materials was regulated in combination with the changes in the content of various surface elements and surface energy.

14. The waterproof protection treatment method for cable sheath PVC material according to claim 13, characterized in that: The chemical reaction between carbon tetrafluoride and polyvinyl chloride material includes dissociation phenomenon, surface grafting phenomenon and decomposition phenomenon; The dissociation phenomenon is a phenomenon in which the chemical bonds are broken due to the collision of free electrons in the chemical reaction between carbon tetrafluoride and polyvinyl chloride materials, and excited atoms or free radicals are generated. The surface grafting phenomenon is that when the bond energy of the CH bond is less than the bond energy of the CF bond and the HF bond, the hydrogen radicals in the free state will combine with the fluorine radicals, and the carbon chain will combine with the remaining fluorine radicals; The decomposition phenomenon is the desorption of carbon tetrafluoride under plasma modification experiment, which leads to the decomposition of carbon tetrafluoride under long-term discharge conditions.

15. The waterproof protection treatment method for cable sheath PVC material according to claim 14, characterized in that: The pulse current decay technology is used to sequentially perform a pulse current decay test and a breakdown voltage band test on the modified polyvinyl chloride material, and combined with the pulse current decay test results and the breakdown voltage band test results, the time-frequency domain dielectric properties of the polyvinyl chloride material are regulated, including: The pulse current decay technology is used to perform a pulse current decay test on the modified polyvinyl chloride material to obtain a pulse current decay curve; The relaxation time constant is obtained by performing spectrum analysis on the pulse current decay curve, and the relaxation time constant is input into the extended Debye model to obtain the trap depth corresponding to the relaxation time constant. The DC conductivity and breakdown voltage of polyvinyl chloride materials are controlled based on the trap depth corresponding to the relaxation time constant; The modified polyvinyl chloride material is subjected to a breakdown voltage band test to obtain the AC breakdown voltage of the polyvinyl chloride material before and after modification, and the bulk insulation of the polyvinyl chloride material is analyzed based on the AC breakdown voltage.

16. Application of the waterproof protection treatment method for cable sheath PVC material according to any one of claims 1 to 15 in hydrophobic protection of polyvinyl chloride materials.

Citation Information

Cited By

  • Re-toughening method of metallic glass

    CN120648872A